2004
DOI: 10.1111/j.1083-4389.2004.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the Helicobacter pylori feoB Gene in Korea: a Possible Relation with Iron‐Deficiency Anemia?

Abstract: The four polymorphisms of the feoB gene observed appear to be related to the clinical phenotype of IDA, but the relation is unclear because of the small number of strains studied. Further studies are required to confirm a correlation between IDA and H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…Proteomic analysis of 15 strains (7 from IDA patients and 8 from non-IDA patients) revealed that IDA strains phylogenetically clustered together and separately from the non-IDA strains (105). Additionally, in a study of IDA strain isolates compared to non-IDA isolates, the strains from IDA patients showed increased uptake of both Fe(II) and Fe(III) (131); while the reason for this increased iron uptake is not known, certain polymorphisms in feoB, a ferrous iron transporter, have been shown to occur in IDA-derived strains of H. pylori (81). Even though the exact mechanism by which H. pylori and IDA are linked is not well understood, it is highly likely that Fur plays some role in this process, as it is the primary regulator of iron uptake and storage genes in this organism.…”
Section: H Pylori and Iron-associated Diseasementioning
confidence: 99%
“…Proteomic analysis of 15 strains (7 from IDA patients and 8 from non-IDA patients) revealed that IDA strains phylogenetically clustered together and separately from the non-IDA strains (105). Additionally, in a study of IDA strain isolates compared to non-IDA isolates, the strains from IDA patients showed increased uptake of both Fe(II) and Fe(III) (131); while the reason for this increased iron uptake is not known, certain polymorphisms in feoB, a ferrous iron transporter, have been shown to occur in IDA-derived strains of H. pylori (81). Even though the exact mechanism by which H. pylori and IDA are linked is not well understood, it is highly likely that Fur plays some role in this process, as it is the primary regulator of iron uptake and storage genes in this organism.…”
Section: H Pylori and Iron-associated Diseasementioning
confidence: 99%
“…These include competition between the pathogen and host for limited iron stores [13], [17], [18], particularly in individuals with iron poor diets, thus exacerbating the effects of reduced iron intake. Iron is essential for H. pylori growth and survival, but this pathogen does not produce siderophores conventionally used by other bacteria to acquire iron [19].…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation of iron transport and storage proteins in H. pylori renders it incapable of host colonisation. H. pylori iron binding proteins have also been implicated in the aetiology of IDA [18], [21]. Hypochlorhydria associated with acute H. pylori infections may predispose to IDA due to the inability to generate the bioavailable, reduced form of iron (ferrous, Fe 2+ ) under non-acidic conditions [22], [23], [24].…”
Section: Introductionmentioning
confidence: 99%
“…Infection of humans with H. pylori precipitates iron deficiency, and afflicted patients are recalcitrant to iron replacement therapy until the pathogen is cleared (Barabino, 2002;Cardamone et al, 2008;Mulayim et al, 2008). Although little is known of the pathological association between iron deficiency and H. pylori infection, it is known that H. pylori strains isolated from iron-deficient patients display increased uptake of iron as well as polymorphisms in feoB, a ferrous iron transporter (Jeon et al, 2004;Yokota et al, 2008). Fur is likely complacent in H. pylori pathogenesis (Carpenter et al, 2009): Although mutagenesis experiments involving H. pylori have shown that presence of Fur is not essential to life (Chalker et al, 2001), it is important for virulence (Bury-Moné et al, 2004;Gancz et al, 2006).…”
Section: Prolificacy Of Helicobacter Pylori and Mycobacterium Tubercumentioning
confidence: 99%